Immunotoxicity of Carbon-Based Nanomaterials, Starring Phagocytes - Svadlakova, Tereza; Holmannova, Drahomira; Kolackova, Martina; Malkova, Andrea; Krejsek, Jan; Fiala, Zdenek (International journal of molecular sciences, 2022)
In the field of science, technology and medicine, carbon-based nanomaterials and nanoparticles (CNMs) are becoming attractive nanomaterials that are increasingly used. However, it is important to acknowledge the risk of nanotoxicity that comes with the widespread use of CNMs. CNMs can enter the body via inhalation, ingestion, intravenously or by any other route, spread through the bloodstream and penetrate tissues where (in both compartments) they interact with components of the immune system. Like invading pathogens, CNMs can be recognized by large numbers of receptors that are present on the surface of innate immune cells, notably monocytes and macrophages. Depending on the physicochemical properties of CNMs, i.e., shape, size, or adsorbed contamination, phagocytes try to engulf and process CNMs, which might induce pro/anti-inflammatory response or lead to modulation and disruption of basic immune activity. This review focuses on existing data on the immunotoxic potential of CNMs, particularly in professional phagocytes, as they play a central role in processing and eliminating foreign particles. The results of immunotoxic studies are also described in the context of the entry routes, impacts of contamination and means of possible elimination. Mechanisms of proinflammatory effect depending on endocytosis and intracellular distribution of CNMs are highlighted as well.
Keywords: monocytes; uhlík; carbon-based nanomaterials; immunotoxicity; nanostruktury; inflammasome; macrophages; carbon nanotubes; Macrophages; Nanostructures; graphene; immunomodulation; Carbon; makrofágy